Determinants of Professional Success – About the Beliefs of Primary School Students - Kozielska, Joanna Wanda (Przegląd Badań Edukacyjnych (Educational Studies Review), 2023)
The paper focuses on the issue of professional success and its perception. The study, carried out using the diagnostic survey method, covered 1099 respondents – students at primary schools, residing in a medium-sized city in Poland. It solved the following research problems: How do youth perceive life and professional success? What associations do male and female students of primary and secondary schools have about post-primary education (vocational/trade school, technical vs. comprehensive school)? What educational pathways do students perceive as prestigious and not prestigious, as enabling professional success and preventing the same? Which professions do students at primary schools perceive as prestigious and non-prestigious? What, in young people’s opinion, are the conditions conducive to professional success? What is the youth’s self-esteem in terms of opportunities to achieve professional success? How do selected socio-demographic characteristics differentiate the perception of professional success, its determinants, and self-esteem concerning the chances of achieving it? An alarming fact is that the beliefs of nearly half the students from the present research sample appear to be that to achieve success, it is necessary to have connections or luck. This arouses concern because, in the expectation of chance, luck (in case of lack of connections) students may adopt a passive attitude in the context of creativity and in fact “moving forward (without their active participation)” in their educational and professional careers.